2018
DOI: 10.1111/ctr.13202
|View full text |Cite
|
Sign up to set email alerts
|

Sinus node dysfunction after heart transplantation—An analysis of risk factors and atrial pacing burden

Abstract: We identified the biatrial anastomosis and a low ratio of reperfusion time to aortic cross-clamp time as well as to ischemia time as risk factors for SND requiring pacing. After implantation pacemakers continue to pace for over 60% of the time after 6 years.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 20 publications
0
8
1
Order By: Relevance
“…Prolonged ischemic time has previously been reported to be associated with bradyarrhythmias after HTX as hypoxia during surgery can cause damage to the sinus node and the electrical conduction system of the cardiac allograft (1,4,28). However, we and other recent studies could not detect a significant association between ischemic time and PPM implantation after HTX (5,7,(11)(12)(13).…”
Section: Risk Factors For Ppm Implantation After Htxcontrasting
confidence: 93%
See 2 more Smart Citations
“…Prolonged ischemic time has previously been reported to be associated with bradyarrhythmias after HTX as hypoxia during surgery can cause damage to the sinus node and the electrical conduction system of the cardiac allograft (1,4,28). However, we and other recent studies could not detect a significant association between ischemic time and PPM implantation after HTX (5,7,(11)(12)(13).…”
Section: Risk Factors For Ppm Implantation After Htxcontrasting
confidence: 93%
“…Due to the lack of organ donation, it is essential to continuously improve quality of life and to search for risk factors which may impair survival after HTX (11).…”
Section: Post-transplant Survival and Causes Of Deathmentioning
confidence: 99%
See 1 more Smart Citation
“…While the effect of amiodarone on heart rate cannot be excluded, the difference in HR between the groups remained significant after adjustment for amiodarone treatment in multivariate analysis. Sinus node dysfunction is a common complication in the early post‐HTx setting, sometimes requiring permanent pacemaker placement, and has been linked to ischemia‐reperfusion injury . Some studies suggest alcohol increases donor heart susceptibility to this type of injury .…”
Section: Discussionmentioning
confidence: 99%
“…In 2015, the Food and Drug Administration issued a warning against the concomitant use of amiodarone and sofosbuvir‐containing DAA regimens 20 . Despite being supported primarily by case reports and further limited by concomitant beta‐blocker use, these reports are concerning due to the risk for sinus node dysfunction post–heart transplant 20,21 . A prior study reported the safe use of sofosbuvir‐velpatasvir and concomitant amiodarone in 3 HCV NAT+ heart transplant recipients, although there were no details on the duration of treatment overlap and the degree of monitoring during therapy 9 .…”
Section: Discussionmentioning
confidence: 99%